Prediction of Neurologic Deterioration in Patients with Lacunar Infarction in the Territory of the Lenticulostriate Artery Using Perfusion CT - Yamada, Mikito (AJNR Am J Neuroradiol, 2004)
BACKGROUND AND PURPOSE: A significant proportion of patients with lacunar infarctions experience neurologic deterioration after onset. However, no clinical examination has been established for prediction of the progress of symptoms. To determine the hemodynamic predictors of such progression, we performed perfusion CT to quantitatively assess cerebral blood flow (CBF), cerebral blood volume (CBV), and mean transit time (MTT) of patients with lacunar infarctions in the territory of the lenticulostriate artery. METHODS: We performed MR imaging and perfusion CT of 26 patients with lacunar infarction within 24 hr after onset. On the CBF map on perfusion CT scans, a round small region of interest was set at the region, with decreased CBF in the territory of the lenticulostriate artery (region of interest 1). Another region of interest was set in the mirror position to region of interest 1 in the contralateral hemisphere (region of interest 2). Using these two regions of interest, CBF, CBV, and MTT were measured. All patients underwent neurologic and MR imaging follow-up while receiving equivalent medical treatment. RESULTS: Neurologic deterioration after onset was shown in 13 patients (progress group), whereas no neurologic deterioration was shown in the other 13 patients (control group). In the progress group, lacunar infarctions were enlarged on follow-up MR images. The ratio of region of interest 1/region of interest 2 showed significantly lower CBF and higher MTT in the progress group than in the control group. CONCLUSIONS: These results suggest that progressive lacunar infarction in the territory of the lenticulostriate artery could be predicted with a higher MTT ratio (>1.26) and a lower CBF ratio (<0.76) on perfusion CT scans obtained within 24 hr after onset.